Coral Community Structure at The Intertidal Zone of Serinting Beach Special Economic Zone (SEZ) of Mandalika - Ainiyawati, Yeni; Bachtiar, Imam; Suyantri, Eni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Serinting Beach is located within the Special Economic Zone of Mandalika, where ongoing massive tourism facility development may impact the intertidal coral communities. The intertidal zone of Serinting Beach is also a primary location for reef gleaning, which impacts corals in the intertidal area. Considering that corals are the foundational components of reef ecosystems, the prospective development of this designated super-priority tourism area may exert significant impacts on the intertidal coral communities. This investigation aimed to delineate the coral community structure within the intertidal zone of Serinting Beach, situated in the Mandalika Special Economic Zone (SEZ). Sampling was executed via the transect-quadrat method. Measured variables encompassed coral life forms, genera, families, and the respective colony counts. The study identified 323 coral colonies distributed among 17 genera and 9 families. Compositions of three predominant genera were Heliopora 25.39%, Favites 24.77%, and Porites 22.91%. The Faviidae family exhibited the highest compositional abundance, contributing 37.15%, followed by Helioporidae 25.39% and Poritidae 23.53%. Furthermore, eight distinct coral life forms were documented in the intertidal zone, with massive coral representing the predominant form at 35.60%, followed by coral encrusting 26.01%, and blue coral 25.39%. Ecological indices indicated a moderate level of coral diversity (H'=1.98), accompanied by an unstable evenness index (E=0.70) and a low dominance index (C=0.19).